OPTIMALISASI OPTIMALISASI GERAKAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA DI SEKOLAH DASAR: Strategi Peningkatan Minat Baca Siswa Sekolah Dasar Melalui Optimalisasi Program Gerakan Literasi Sekolah - hafizha, hafizha; Rokmanah, Siti; Andriana, Encep (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The low literacy rate in Indonesia, especially regarding reading, hinders educational progress. Low interest in reading, especially among elementary students school, is a contributing factor. Literacy is a fundamental skill in education, including the capacity to read, write, understand, analyze, and put knowledge to use from various sources. Even the though School-Based Literacy Movement (GLS) has been implemented, there are still many challenges in fostering a reading culture among elementary school students. This study, which is an (SLR) Systematic Literature Review, investigates effective strategies for optimizing the primary elements that affect literacy success programs. Research findings show that a combination of strategy, regular evaluations, and a supportive learning environment are critical to increasing student’s reading interest and overall literacy skills. The study highlights the necessity of taking a more comprehensive approach to literacy development, involving not only schools but also parents and communities. This research aims to explore strategies to optimize GLS and increase student’s interest in reading by analyzing various approaches and interventions, which contribute to better literacy policies and practices in elementary schools.